Antlers on does: An unexpected role of macrophages in deer biology - Datao Wang; Hengxing Ba; Xunsheng Li; Tomas Landete-Castillejos; Wanwan Shi; Zhen Wang; Jing Ren; Hongmei Sun; Louis Chonco; Chao Ma; Guokun Zhang; Gerry Melino; et al. (Proceedings of the National Academy of Sciences, 2025)
Antlers, a male deer secondary sex characteristic, are unique mammalian appendages that fully regenerate annually, under androgen regulation. Stem cells located in the antlerogenic periosteum (AP), a tissue overlaying the frontal crest of both male and female deer, play a crucial role in antlerogenesis. Nonetheless, the underlying molecular mechanisms as to how antlerogenesis is regulated by androgens remain largely unexplored. Here, we show that androgens regulate antler growth via macrophages. Bulk RNA sequencing revealed a significant enrichment of immune-related factors in the androgen-activated antlerogenic periosteum (AAP), and single-cell RNA sequencing identified a cluster of AAP cells overexpressing macrophage chemokine CCL2. Additionally, the presence of a substantial number of monocytes/macrophages was detected in the skin overlying the AAP. Histological examination confirmed macrophage accumulation in the AAP. Removal of macrophages with clodronate effectively inhibited antler generation in male sika deer as well as in nude mice engrafted with the AP. Furthermore, testosterone up-regulated CCL2 expression in the AP cells (APCs), thus enhancing their chemotactic effect on recruitment of macrophages. Remarkably, female sika deer developed antlers following local injection of CCL2, autologous macrophages, or even immune response inducer lipopolysaccharide (LPS). Therefore, macrophages play an essential role in deer antler generation.